2002
DOI: 10.1292/jvms.64.441
|View full text |Cite
|
Sign up to set email alerts
|

CD56 is Expressed Exclusively on CD3+ T Lymphocytes in Canine Peripheral Blood.

Abstract: ABSTRACT. CD56+ cells in canine blood leukocytes were characterized by flow-cytometric analysis of peripheral blood of 30 healthy adult beagle-dogs (15 males and 15 non-pregnant females). In 19 of the 30 dogs, anti human CD56 antibody, reacted CD56, which is a neural cell adhesion molecule (N-CAM), is a membrane glycoprotein belonging to the immunoglobulin superfamily [3,8]. CD56 is expressed mainly on natural killer (NK) cell in human peripheral blood and is used as a surface marker of human NK cell [2]. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The human hepatic NK cells are generally considered to contribute to antiviral, tumoricidal and pathogenic inflammatory responses [13]. However, as any specific surface antigenic molecules have never been identified in the canine NK cells at present [6,8], significant relation of non-T non-B lymphocytes and NK cells in canine liver was not able to be clearly defined in this study.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…The human hepatic NK cells are generally considered to contribute to antiviral, tumoricidal and pathogenic inflammatory responses [13]. However, as any specific surface antigenic molecules have never been identified in the canine NK cells at present [6,8], significant relation of non-T non-B lymphocytes and NK cells in canine liver was not able to be clearly defined in this study.…”
mentioning
confidence: 71%
“…After diluting to 1:10 with FCM-buffer, and the samples were immediately acquired by FACS Calibur (Becton-Dickinson, Franklin Lakes, NJ). The lymphocytes were separated from the other cells by gating on the forward scatter versus side scatter dot plot of FACS Calibur [3,5,8]. Fluorescence intensity of 7-AAD in gated lymphocytes was detected at 630 nm (FL-3 on FACS Caliber).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ehrlichia infection was ruled out based on serology. Flow cytometric analysis was performed using monoclonal antibodies as described previously [9]. The results indicated that most peripheral blood lymphocytes (PBLs) were of the CD3+8+ phenotype (Figs.…”
mentioning
confidence: 99%
“…CD56 is suggested to be expressed in canine lymphocytes [21]; however, the dynamics of CD56 in peripheral blood is not well understood. The CD56 expression level could be used for a mirror of NK activity if it is supposed to be specifically expressed in canine NK cells.…”
mentioning
confidence: 99%